Re‐Embedding Trade in the Shadow of Populism - Kolben, Kevin (2023)
In the last 75 years of international economic cooperation, we have witnessed tremendous changes. The global trade and investment regime is under pressure and undergoing a significant transformation. Supply chains are being restructured, new trade blocks are forming based on strategic and political considerations, support for trade among citizens is weak and inconsistent, and populist opposition to the global economic and political order is ascendant. In this time of uncertainty about the future of the world order, the articles for this thematic issue address how and if the global trade and investment regime can be re-embedded into society.